The circular economy, design thinking and education for sustainability - Andrews, Deborah (Local economy, 2015)
The origins of the Linear Economy – the ‘take-make-use-dispose’ model of consumption – date from the Industrial Revolution and the global economy developed around this model. Various social, economic and environmental factors mean that it is no longer sustainable. A radical new model – the Circular Economy – is being advocated but as yet it is not widely practiced. This paper proposes that designers are crucial to the development of this new economic model; furthermore, this model facilitates education for sustainability and enhances employability.